Respostas
respondido por:
38
{x=11-y (i)
{x.y=18 (ii)
(i) em (ii)
(11-y)*y=18
y²-11y+18=0
y'=[11+(121-72)¹]/2=9
y''=[11-(121-72)¹]/2=2
Se y=9 ==>x=11-9=2
Se y=2 ==>x=11-2=9
Resp:{(2,9),(9,2)}
espero ter ajudado :D
{x.y=18 (ii)
(i) em (ii)
(11-y)*y=18
y²-11y+18=0
y'=[11+(121-72)¹]/2=9
y''=[11-(121-72)¹]/2=2
Se y=9 ==>x=11-9=2
Se y=2 ==>x=11-2=9
Resp:{(2,9),(9,2)}
espero ter ajudado :D
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás